If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = 4(0) + -3 Multiply 4 * 0 -4 = 0 + -3 Anything times zero is zero. -4 = 0 + -3 Combine like terms: 0 + -3 = -3 -4 = -3 Solving -4 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6y-1=5y+2 | | 8c+5=4-11 | | 4x+28=-4 | | (4z-3)(z+6)-(4z-3)(z-5)= | | 50x-811=78 | | m-9m+3m+9= | | 3.33x-16=74 | | 12-2y=-4 | | 6(7(-6)-1)=43(-6) | | 19w^2-25w-44=0 | | -6x^2+25x-14=0 | | 7x-4=2x+11 | | 2+x=67 | | 4w-30y= | | 9-5y=41 | | 8u-2(u-8)=2u | | 20y^2-19y-28=0 | | 14x^2+98x+140=0 | | 3x-3y=1 | | 4x-10=5(x-2) | | -16=-8-y | | -4(4w+y)-5(6y-4w)= | | 1/8(9+h)=2 | | 2(-3)+5y=3 | | 6+2x=-14 | | 1/5(750+d)=350 | | 1/5(750+d)=290 | | 17x+6=4(4x+6) | | 150x+200(15-x)=2500 | | 7y=5y+8 | | -4+30= | | -4+-30= |